Study of cadmium adsorption from aqueous solution on activated carbon from sugar beet pulp - Özer, Ahmet; Tanyıldızı, Muhammet Şaban; Tümen, Fikret (My University, 1998)
The adsorption ability of activated carbons from sugar beet pulp to remove the cadmium from aqueous solutions has been investigated. Optimum temperature and time for carbonization of sugar beet pulp were determined as 700 °C and 120 min. The results of adsorption experiments show that pH for effective removal of cadmium was 6.3 or greater. The maximum removal percentage of cadmium were found to be 99.0, 78.2 and 57.0 by using 2.5 g l?1 adsorbent dosage for initial cadmium concentration of 100, 250 and 500 mg l?1, respectively, at optimum pH and 20 °C for a contact time of 120 min. Langmuir and Freundlich adsorption models were applied to the isotherm data. The free energy change of process was found to be ?18.03 Kj mol?1.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Cadmium removal; Sugar beet pulp; Carbonization; Adsorption; Adsorption isotherm